Incidental axillary dose delivery to axillary lymph node levels I–III by different techniques of whole-breast irradiation: a systematic literature review - Schmitt, Martin; Pin, Yvan; Pflumio, Carole; Mathelin, Carole; Pivot, Xavier; Noel, Georges (Strahlentherapie und Onkologie, 2021)
Background and objective In breast cancer treatment, radiotherapy is an essential component for locoregional management. Axillary recurrence in patients with invasive breast carcinoma remains an issue. The question of whether breast irradiation may unintentionally include levels I, II, and III, and may decrease the risk of axillary recurrence, remains a topic of discussion. Patients and methods A literature search was performed in PubMed and the Cochrane Library to identify articles that have published data regarding dose–volume analysis of axillary levels in breast irradiation. The following MESH terms were used: “breast cancer/lymph nodes” AND “radiotherapy dosage.” Results Thirteen articles were identified. The irradiation technique, initial dose prescribed to the breast, delineated volumes, and dose received at axillary levels were heterogeneous. The average dose delivered to axilla levels I, II, and III with three-dimensional conformal radiotherapy using standard fields (ST) ranged between 22 and 43.5 Gy, 3 and 35.6 Gy, and 1.0 and 20.5 Gy, respectively. The average doses delivered to axilla levels I, II, and III with three-dimensional conformal radiotherapy using “high tangential” fields (HT) ranged between 38 and 49.7 Gy, 11 and 47.1 Gy, and 5 and 44.7 Gy, respectively. Finally, the average doses delivered to axilla levels I, II, and III using intensity-modulated radiation therapy (IMRT) were between 14.5 and 42.6 Gy, 3.4 and 35 Gy, and 1.2 and 25.5 Gy, respectively. Conclusion Our literature review suggests that the incidental dose delivered to the axilla during whole-breast irradiation is heterogenous and dependent on the irradiation technique used. However, whether this observation can be translated into a therapeutic effect is still a matter of debate.